Use of ozone to optimize tissue repair after complications in oral surgery: case report (Research, Society and Development, 2020)
Ozone therapy has been used as adjuvant therapy in multiple therapeutic modalities in dentistry. Characterized by few adverse effects at therapeutic doses, ozone is associated with the formation of reactive oxygen molecules that influence cellular metabolism and trigger an antioxidant response, favouring tissue repair, in addition to having an antimicrobial effect. Several studies prove the health benefits of ozone. The objective of this work is to report the benefit of using ozone to aid the regeneration of avulsioned gingival tissue in a traumatic way after performing a lower third molar extraction, where the irrigation of ozonized water in a concentration of 8µg / ml was instituted as treatment and application of ozone gas for a period of four weeks. After 14 months of follow-up, the gingival tissue showed no signs of ischemia, necrosis and infection, with total repair of the affected area.